2007
DOI: 10.1111/j.1524-475x.2007.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Wound‐healing factors secreted by epidermal keratinocytes and dermal fibroblasts in skin substitutes

Abstract: Full-skin substitutes, epidermal substitutes, and dermal substitutes are currently being used to heal deep burns and chronic ulcers. In this study, we investigated which wound-healing mediators are released from these constructs and whether keratinocyte-fibroblast interactions are involved. Autologous skin substitutes were constructed from human keratinocytes, fibroblasts, and acellular donor dermis. Full-thickness skin was used to represent an autograft. Secretion of wound-healing mediators was investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
131
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 35 publications
7
131
0
Order By: Relevance
“…Many fibroblasts remain in the lower regions of the dermis, with few cells migrating into the upper regions. However, as we have previously shown that soluble mediators HGF, IL‐6, CCL2, CCL5 and CXCL8 are secreted by SS only when fibroblasts are present (Spiekstra et al, 2007) and as we show that vimentin is detectable in both SS and GS, we can conclude that viable fibroblasts as well as epithelial cells are present in SS and GS.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Many fibroblasts remain in the lower regions of the dermis, with few cells migrating into the upper regions. However, as we have previously shown that soluble mediators HGF, IL‐6, CCL2, CCL5 and CXCL8 are secreted by SS only when fibroblasts are present (Spiekstra et al, 2007) and as we show that vimentin is detectable in both SS and GS, we can conclude that viable fibroblasts as well as epithelial cells are present in SS and GS.…”
Section: Discussionsupporting
confidence: 78%
“…The major advantage of living skin and oral mucosa substitutes over acellular dressings and biomaterials is their capability to function as a living pump, continuously secreting a cocktail of cytokines, chemokines and growth factors, which promote angiogenesis, granulation tissue formation and re‐epithelialization (Spiekstra, Breetveld, Rustemeyer, Scheper, & Gibbs, 2007). However, no human tissue‐engineered oral substitutes for clinical oral applications are yet commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous gingiva had become submerged in culture medium a very strong keratin 13 expression was observed. This findings indicate that the presence of fibroblasts in the dermis in addition to an epithelium will stimulate angioindicates that, in contrast to the other gingiva markers, keratin 13 may be regulated by environmental factors genesis, and therefore wound healing, more than a construct containing only an epithelium (38). Indeed, we (e.g., saliva) rather than intrinsically.…”
Section: Discussionmentioning
confidence: 95%
“…1 Skin substitutes have the ability to deliver cytokines, chemokines, growth factors and competent cells at wound site, thus improving the wound closure. 2,3 Definitive treatment of extensive burns requires that autologous skin be used since other allogenic grafts are rejected after several days/weeks. In a context of the production of engineered living skin substitutes, the use of the patient's own cells oversteps immune incompatibility problems but requires that the production of such skin constructs be initiated only after isolating patient's cells.…”
Section: Introductionmentioning
confidence: 99%